A CASE STUDY OF STUDENTS’ PERCEPTIONS ON REWARD AND PUNISHMENT GIVEN BY THEIR ENGLISH TEACHER - Anisa Toharoh Nurhuda; Erna Wardani; Weksa Fradita Asriyama (LEAD (Language, Education and Development), 2021)
This research generally deals with reward and punishment in English teaching. It is mainly concerned with (1) the types of reward and punishment often given by English teachers, (2) students’ perceptions on reward and punishment given by their English teacher, (3) students’ feedback on reward and punishment given by their English teacher. The data were collected using questionnaire, interview, and observation. The data analysis was performed through the selection and transcription of the data related to the research objectives. The data were then presented descriptively. The results of this research indicate that (1) 80% of the students mention that the types of reward and punishment often given by their English teacher are praise, tribute, recommendation and commands, and notice, (2) 84% of the students claim that reward and punishment are important in English teaching, and based on the students’ feedback, (3) 76% of the students become more motivated in learning after receiving reward and punishment given by their English teacher. These findings suggest that reward and punishment has a significant effect on building up students’ motivation to learn and upgrading their academic achievement (grades).